Chronicle of Gerontogeriatry in Santiago de Cuba - Juana Adela Fong Estrada (Centro Provincial de Información de Ciencias Médicas, 2020)
Gerontology studies the aging process and Geriatrics is in charge of the clinical, therapeutic, preventive and social aspects, in the health and disease of the elderly. Its emergence in the world, the country and its development in Santiago de Cuba province is exposed, as well as the experiences of the pioneers in this specialty.